ANALISA METODE TREND MOMENT UNTUK PERAMALAN PENJUALAN STOK BARANG PADA TOKO SUN OLEH-OLEH - Ayu Nanda Safitri; Fricles A Sianturi (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2020)
Sun Souvenirs Shop is a private company that sells souvenirs. The Sun Souvenir Shop has a wide variety of typical Medan food and souvenirs for sale. Customers who don't have time to buy souvenirs outside can buy them at Kualanamu International Airport. Sun Souvenir Shop is located at Departure Level 2 near the check-in counter. This research is about forecasting system. The method used is the Trend Moment Method, Trend Moment Method is used to be able to solve the problem, namely to predict sales of stock items. The data used in this study are sales data from the past obtained from interviews conducted directly at the research site. The more data used in forecasting using the Trend Moment method, the more accurate the resulting forecast will be. The system was built using the Visual Studio 2010 programming language with Microsoft Access 2007 database. The result of this research is a forecasting application that can assist in predicting sales of stock items.